A Dynamic Analysis of the Effects of a Price Support Program on Price Dynamics and Price Volatility - Kwansoo Kim; Jean-Paul Chavas (Journal of Agricultural and Resource Economics, 2002)
This study presents an econometric analysis of the effects of a government price support program on price dynamics and price volatility. Price support programs, a common feature of agricultural policy, provide a lower-bound censoring of the distribution of market prices. An econometric model of market prices is developed using a dynamic Tobit specification under time-varying volatility. The model is applied to the U.S. non-fat dry milk market. It is used to investigate the impact of market liberalization on price dynamics and price volatility in the presence of private and public stocks. The econometric results show how the price support program and stocks (both private and public) affect expected price volatility.